PERFORMANCE EVALUATION OF REGIONAL RURAL BANKS (RRBS) IN INDIA DURING PRE AND POST AMALGAMATION PERIOD - Megha and Aparna Bhatia (Abhigyan, 2013)
Regional rural banks (RRBs) provide rural credit in rural sectors to small and marginal farmers, agricultural labourers, socio-economically weaker sections of population for development of agriculture, trade, commerce, industry and other productive activities in India. In order to improve the operational viability of Regional Rural Banks (RRBs) and take advantage of the economies of scale the route of amalgamation of Regional Rural Banks (RRBs) was suggested in 2005. The present paper evaluates the performance of Regional Rural Banks (RRBs) in terms of spread, burden and profitability over the study period. It also studies the growth pattern in spread, burden and profitability of Regional Rural Banks (RRBs) over the base year. Another, objective of the paper is to determine whether the performance of Regional Rural Banks (RRBs) significantly differs from pre amalgamation period and post amalgamation period. All the RRBs in India constitute the sample of the study. The study covers the time period of 11 years i.e. 2000-01 to 2010-11 to study the performance and analyze the growth pattern. The entire period has been divided into two parts as 2001-02 till 2004-05 and 2006-07 till 2010-11 to study whether amalgamation process of Regional rural banks (RRBs) resulted in significant difference in their performance. The results show that the overall position of Regional Rural Banks (RRBs) in India has improved in the post amalgamation period, even though number of Regional rural banks (RRBs) has decreased and the branch network has increased. The spread ratios have increased in the post amalgamation period while there is decrease in the burden ratios. Even the t values of paired t-test are significant for all the ratios of spread at 5 percent level of significance.